Current Practices in Cold Regions Engineering 2006
DOI: 10.1061/40836(210)44
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Frost Heave of THF Clathrate Hydrate on Porous Glass Powder

Abstract: The formation processes of clathrate hydrate in porous glass powder saturated with a THF-water mixture were directly observed using directional cooling apparatus. As the cooling rate decreased, the THF hydrate grew while excluding glass particles and formed a lens like layer of hydrate in the same manner as in the phenomenon of ice lens formation in the freezing of soil. The growth rate of the hydrate lens was proportional to the degree of supercooling of the growth surface and was about 1/20th the growth rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…The result shows that, although the velocity controlled the cooling rate, R was smaller than V . As a result, the growing hydrate layer was supercooled compared with the equilibrium temperature in the porous media, as reported by Watanabe et al…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…The result shows that, although the velocity controlled the cooling rate, R was smaller than V . As a result, the growing hydrate layer was supercooled compared with the equilibrium temperature in the porous media, as reported by Watanabe et al…”
Section: Resultssupporting
confidence: 58%
“…Watanabe et al also reported an identical dependence of the ice lens thickness on R . However, the interval between the ice lenses was not found to be dependent on R (the size scales of THF hydrate layers were not shown). The results in the present study were obtained by measuring periodic hydrate layers during steady-state growth.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…[5] While there have been some focused laboratory efforts [e.g., Watanabe et al, 2006], no study has ever systematically documented the volume changes associated with hydrate formation and dissociation in different soils, at a range of effective stress, and for hydrate saturations ranging from 0% to 100% of pore space. This study seeks to fill this gap by measuring the volume change associated with formation and dissociation of tetrahydrofuran (THF) hydrate, which is fully miscible in water.…”
Section: Introductionmentioning
confidence: 99%
“…This situation is exacerbated in clayey sediments where methane transport may be diffusion limited, and where the scale of devices must allow for hydrate segregation and lens formation. THF and ice analogs (Watanabe et al, 2006) used to explore lensing have fundamental differences (e.g., methane-transport limited vs. heat-diffusion limited), but do share some important underlying phenomena (e.g., capillary control, cryogenic suction and stress-field effects).…”
Section: Introductionmentioning
confidence: 99%